A qualitative exploration of the impacts of COVID-19 in two rural Southwestern Alaska communities - Katie Cueva; Malory Peterson; Ay’aqulluk Jim Chaliak; Rebecca Ipiaqruk Young (International Journal of Circumpolar Health)
This manuscript presents a qualitative exploration of the experiences of people in two Southwestern Alaska communities during the emergence of COVID-19 and subsequent pandemic response. The project used principles of community based participatory research and honoured Indigenous ways of knowing throughout the study design, data collection, analysis, and dissemination. Data was collected in 2022 through group and individual conversations with community members, exploring impacts of the COVID-19 pandemic. Participants included Elders, community health workers, Tribal council members, government employees, school personnel, and emergency response personnel. Notes and written responses were coded using thematic qualitative analysis. The most frequently identified themes were 1) feeling disconnected from family, friends, and other relationships, 2) death, 3) the Tribal councils did a good job, and 4) loss of celebrations and ceremonies. While the findings highlighted grief and a loss of social cohesion due to the pandemic, they also included indicators of resilience and thriving, such as appropriate and responsive local governance, revitalisation of traditional medicines, and coming together as a community to survive. This case study was conducted as part of an international collaboration to identify community-driven, evidence-based recommendations to inform pan-Arctic collaboration and decision making in public health during global emergencies.